Analisis Pemberian ASI Eksklusif oleh Ibu Menyusui di Puskesmas Tanjung Agung Kabupaten OKU - Desiana Nafisa; Chairil Zaman; Helen Evelina Siringoringo (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2022)
Health is a human right and one of the elements of welfare that must be realized. One of them is that every baby has the right to get exclusive breast milk from birth for 6 (six) months. The purpose of this study was to look at the factors associated with patient satisfaction. This study uses a quantitative method with a Cross Sectional approach. Statistical test using Chi Square test. Multivariate analysis in this study used multiple logistic regression analysis. In this study, it can be concluded that there is no relationship between age (p = 0.583), knowledge (p = 0.065), information exposure with exclusive breastfeeding at the Tanjung Agung Health Center, OKU Regency in 2021 (p = 0.051). There is a relationship between education (p = 0.036; OR = 3.734), occupation (p = 0.029; OR = 2.884), parity (p = 0.030; OR = 3.128), family support (p = 0.033; OR = 2.899) and support for health workers (p = 0.044; OR = 0.364) with exclusive breastfeeding at the Tanjung Agung Health Center, OKU Regency in 2021. The most dominant variable is education (p = 0.005; OR = 8.385). The findings of this study can be used by health centers, especially in OKU Regency so that respondents can educate respondents to provide input so that they want to give exclusive breastfeeding